Internship program to improve student competence in managing the Gedung Sate Museum - Cindy Cantika Dwi Oktaviani (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2025)
Technological developments have accelerated, accompanied by digital transformation across various sectors. This compels individuals to continually adapt by improving their skills to meet workplace needs. The implementation of community service through internships aims to facilitate students' application of what they have learned during their studies. This community service is implemented through the Penguatan Pengalaman Profesional Non-Kependidikan (P3NK) program, organized by the university, to enhance students' competencies and gain work experience outside the campus. In this activity, the P3NK program is implemented by training students to become educators and museum receptionists, to introduce visitors to audiovisual rooms, and to create Instagram captions for each post. The implementation of this activity has proceeded smoothly, with effective coordination and communication between the museum and the interns. This internship is an important step for students to apply the knowledge they have learned on campus while simultaneously playing an active role in preserving local history and culture.   Abstrak Perkembangan teknologi saat ini telah meningkat dengan pesat diiringi dengan transformasi digital di berbagai sektor. Hal ini memaksa setiap individu untuk dapat seseorang untuk terus beradaptasi dengan meningkatkan kemampuan yang dimiliki sesuai dengan kebutuhan dalam dunia kerja. Pelaksanaan pengabdian melalu kegiatan magang bertujuan untuk memfasilitasi mahasiswa dalam melakukan atau mempraktekkan apa yang telah dipelajarinya selama di bangku perkuliahan. Metode pelaksanaan pengabdian ini melalui program Penguatan Pengalaman Profesional Non-Kependidikan (P3NK) yang diselenggarakan oleh universitas untuk meningkatkan kompetensi mahasiswa dan mendapatkan pengalaman kerja di luar kampus. Pada kegiatan ini pelaksanaan program P3NK dilakukan dengan melatih mahasiswa menjadi edukator, resepsionis kunjungan museum, perkenalan ruangan audio visua kepada pengunjungl, dan pembuatan caption instagram pada setiap unggahannya. Pelaksanaan kegiatan ini telah berjalan dengan baik dengan adanya koordinasi dan komunikasi yang lancar antara pihak museum dan peserta magang pada setiap kegiatannya. Pelaksanaan magang ini menjadi langkah penting bagi mahasiswa untuk mengaplikasikan ilmu yang telah dipelajari di kampus sekaligus berperan aktif dalam pelestarian sejarah dan budaya lokal. Kata Kunci: kompetensi; magang; museum